Desenvolvimento de compósito epóxi/fibra de vidro produzido por enrolamento filamentar para revestimento interno de coluna de produção de petróleo em aço carbono na exploração offshore - Guimarães, Bárbara Silva Sales (2021)
Epoxy/glass fiber composites (GRE) were produced by filament winding with a view to application as a liner in a carbon steel tube to replace all-metal super duplex stainless steel column in offshore petroleum exploration. Changes in the Litestone 2210E commercial epoxy resin system containing methylnadic anhydride curing agent were carried out by adding 1,4-butanedioldiglycidyl ether (BDDE) as reactive diluent (RD) and excess of benzyltriethyl ammonium chloride (BTEAC) initiator, to improve the fiber wetting during processing and reduce the curing time, respectively. Viscosity measurements performed by plate and plate rotational rheometry showed that the viscosity of the epoxy system decreased with the addition of the RD. Dynamic curing kinetic studies using the Avrami model modified by Jeziorny and Ozawa were carried from differential scanning calorimetry (DSC) analysis. The glass transition temperatures (Tg) of the epoxy systems were measured by DSC and dynamic mechanical analysis (DMA). Increasing the initiator content anticipated the curing process and increased the curing enthalpy, but did not change the curing rate. The incorporation of DR favored the epoxy cure without significant changes in the curing enthalpy, and reduced Tg by approx. 38°C. Flat plates of unidirectional epoxy/glass fiber composites were produced by filament winding and subjected to tensile and flexural tests and scanning electron microscopy (SEM) analysis. The composites showed good wettability and interfacial adhesion and the addition of DR increased the strength and strain at break without significant change in the elastic modulus. The data indicated that the addition of DR is a viable way to optimize the filament winding processing as well as the curing step and thus optimize the mechanical properties of the epoxy/glass fiber composites.